Optimasi Pengaturan pH Developer untuk Meningkatkan Efisiensi Waktu dalam Processing Film di Ruang Gelap Radiologi - Anggraeni, Leny; Candra, Feri Aria; Ichwan, Yas (Poltekkes Kemenkes Semarang, 2023)
Background: Film processing is an activity to obtain a permanent and real picture of a film, which can be seen with the eye in general conditions. The developer fluid is very influential on the image produced in the film. After exposure, it will be placed in the next step, namely the washing process, so as to produce a permanent image and make a diagnosis. Each exposure of washing film from one film to another, there is a difference in processing time. The more films that are processed, the longer the film processing time is required. The purpose of this study is to see the effect of developer pH on inefficient factors that lead to the film processing time in a dark room. Methods: The research design used was experimental with research samples tested on pH developers in the Radiology Installation of RSUD Pesawaran. Result: Calculation analysis, measurement test result of developer pH measurement to the time of generation on the film was the sig. value which was 0,000 and the degree of relationship value was - 0,983. Conclusion: Based on the provisions, the sig. value of 0.000 <0.05 then Ho was rejected or it was stated that there was a relationship between variable X (pH value) and variable Y (Time).